Analysis of Speech, Communication and Autism Disorders and Their Implications for Learning - Zakaria, Alif Muhammad; Zikri, Muhammad; Latipah, Eva (Jurnal Penyuluhan Agama, 2024)
Abstrak: Anak usia sekolah di Indonesia mengalami gangguan bicara dan bahasa dengan persentase sebesar 5-10 %. Anak usia sekolah masuk dalam tahapan perkembangan industry vs inferiority sehingga gangguan bicara dan bahasa akan memiliki dampak yang negatif bagi perkembanganya. Penelitian ini berjenis data kualitatif dengan pendekatan library research yakni memanfaatkan sumber data sekunder berupa dokumentasi yang didapatkan dari artikel, buku, berita, majalah, dan sumber catatan maupun video. Analisis data dilakukan menggunakan content analysis. Hasil penelitian ini menunjukkan bahwa gangguan bicara dan bahasa menjadi salah satu gejala dalam autisme yang dapat dikenali sedari dini mugkin yakni pada usia 16 bulan. Adapun implikasi gangguan bicara dan bahasa terhadap pembelajaran adalah anak akan merasa kurang percaya diri, sulit dalam memecahkan soal matematika dasar dan prestasi akademik buruk. Autisme disebabkan oleh multifaktor dan ditandai awal dengan ketidakmampuan membentuk hubungan sosial atau mengembangkan komunikasi sehingga berdampak buruk pada proses pembelajaran.Abstract: School-age children in Indonesia experience speech and language disorders with a percentage of 5-10%. School-age children enter the industrial vs inferiority stage of development so that speech and language disorders will have a negative impact on their development. This research is a qualitative data type with a library research approach that utilizes secondary data sources in the form of documentation obtained from articles, books, news, magazines, and sources of notes and videos. Data analysis was performed using content analysis. The results of this study indicate that speech and language disorders are one of the symptoms in autism that can be recognized as early as possible, namely at the age of 16 months. The implications of speech and language disorders for learning are that children will feel less confident, have difficulty solving basic math problems and have poor academic performance. Autism is caused by multiple factors and is marked early by the inability to form social relationships or develop communication so that it has a negative impact on the learning process.